Subsurface S-type Granitoid Identification Based on Gravity and Seismic Tomography Models in Pacitan, East Java - Soesilo, Joko; Palupi, Indriati Retno; Raharjo, Wiji; Sutanto Sutanto; Sulistyohariyanto, Faris Ahad; Ekaristi, Kevin Gardo Bangkit; Stiawan, Fandi Budi (EKSPLORIUM, 2018)
Granitoid outcrop has been observed in Montongan, Tulakan Subdistrict, Pacitan District, East Java. Geochemically, granitoid shows peralluminous S-type granitoid which consists of comparable plagioclase and potassium feldspar leading to adamelite and granodiorite variety with andalusite, fine size corundum and cordierite inside. These modal minerals are consistent with its bulk chemical analysis result that shows alumina rich rock. Highly weathered spotted pinkish soil with remaining quartz gravels characterizes its surface. Lateritic pink soil up to more than 25 meters thick covers the granitoid body and this feature is indicative to locate its surface distribution, while its subsurface distribution is remain uncertain. The research aimed to identify granitoid subsurface distribution. To identify the subsurface body, gravity and seismic tomography models were used. According gravity model, the pluton body is 5 km wide which is rootless downward and seems extends eastward. Meanwhile, the north-south seismic tomographic model across Pacitan Region indicates dense solid body override the recent Java subduction zone. The body is assumed to have correlation with surface granitic rock. It supports an idea that there is a micro continent trapped beneath Southern Mountain of East Java.